LEGAL RESPONSIBILITY OF BUSINESS ACTORS IN BLIND BOX (MYSTERY BOX) SALES TRANSACTIONS THAT CAUSE LOSSES FOR CONSUMERS ON SHOPEE (COMPARATIVE STUDY OF CIVIL LAW AND ISLAMIC FIQH) - Nazwa Redzlya Cantika; Farid Wajdi (Inspiring Law Journal, 2025)
E-commerce gives rise to blind box buying and selling with uncertain transaction objects that have the potential to violate sharia principles and consumer protection and give rise to legal liability for business actors. This study examines the concept of legal liability of business actors in blind box buying and selling transactions (mystery boxes) that cause losses to consumers from a civil law perspective, blind box buying and selling transactions (mystery boxes) in relation to the principle of justice and the prohibition of gharar or maisir in the view of Islamic jurisprudence and a comparison between the regulation of legal liability of business actors in blind box buying and selling transactions (mystery boxes) according to civil law and Islamic jurisprudence, and their relevance to consumer protection in the Shopee marketplace. This type of research is normative law with a descriptive character. The methodology applied includes a statutory regulatory approach (Statute Approach). The research materials are sourced from primary data in the form of Islamic Law, including the Qur'an and Hadith (Sunnah of the Prophet), also Civil Law, especially the Consumer Protection Law and related regulations, accompanied by secondary data including textbooks, legal dictionaries, legal journals, and other relevant legal documents. The legal material collection technique was carried out through literature study, then the data processing and review were carried out using qualitative analysis. The results of the study found that the practice of blind box buying and selling still gives rise to legal liability for business actors, both under civil law and Islamic jurisprudence, because the unclear object of the transaction has the potential to violate the valid conditions of the agreement and the principle of justice. In civil law, business actors can be held accountable under the Consumer Protection Law, while in Islamic jurisprudence this practice is considered to contain elements of gharar and maisir and is therefore invalid under sharia. The different approaches have the same goal, namely to protect consumers through transparency, transaction fairness, and business actor accountability.